Blended learning modules for lectures on oral and maxillofacial surgery. Issue 10 (December 2018) - Bock, A.; Modabber, A.; Kniha, K.; Lemos, M.; Rafai, N.; Hölzle, F.
Abstract: Over the last couple of years, new teaching methods have been developed and implemented in German universities, but only rarely in dental schools. The aim of this project therefore was to implement students' requests for such methods to be used in dental education. In 2012, based on an analysis of both quantitative and qualitative requirements, we designed a questionnaire for quantitative analysis, and evaluated a series of lectures on oral and maxillofacial surgery. Based on our findings, we then designed a blended learning module that was gradually integrated into the series. In 2017 we again evaluated the lectures, and rated the module. The two evaluations were then compared using a two-sample z -test. The results showed that students were very satisfied with the approach. They were particularly happy with the surgical videos, which were shown during the lectures and also included in the module, as they helped them to understand the surgical technique. Our survey showed that most of the students were using the online learning program and that it was the resource they preferred. Application of a blended learning approach could satisfy the requirements of the new generation of students, and transform traditional lectures into modern, sustainable, and technology-enhanced learning experiences.